Comment on "mixed convective flow in a multiple port ventilation square cavity with insulated baffle" [case stud. Therm. Eng. 30, (2022) 101785]. (April 2023) - Saha, Sumon; Zisan, HM Toufik Ahmed; Tarafdar, Utpol
Abstract: As mentioned above, the following comments address missing details, erroneous quantitative conclusions, and incorrect mathematical expressions in the study. Consequently, this investigation compares and corrects the publication "Mixed convective flow in a multiple port ventilation square cavity with insulated baffle." [Case Studies in Thermal Engineering 30 (2022) 101785].